Оцінка інтенсивності запальних процесів та деструкції в тканинах пародонту за лабораторним маркером нітрит-аніону в слині - Ріпецька, О.Р.; Денега, І.С.; Гриновець, В.С.; Гисик, М.В. (Таврический медико-биологический вестник, 2012)
Концентрация нитрит-аниона в слюне пациентов с хроническим катаральным и гипертрофическим
гингивитом существенно отличается с группой контроля только на стадиях обострения. В активной
фазе генерализованного пародонтита уровень нитрит-аниона более чем в десять раз превышает
норму. Очевидно уровень нитрит-аниона в слюне отображает не только активность воспалительного
процесса в пародонте, но и глубину деструкции кости альвеолярного отростка. Nitric-anion concentration in saliva in patients with chronic simple and hyprtrophic gingivitis differs from
the control samples significantly only in the stage of exacerbation. Increased amounts of nitrite-anion in saliva,
more than ten times the healthy control, have been reported in active stage of chronic generalized periodontitis.
A level of nitric-anion in the saliva probably depicts not only the activity of periodontal inflammatory process,
but also the aggressiveness of alveolar bone destruction.